2009
DOI: 10.1523/jneurosci.3561-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

No Nogo66- and NgR-Mediated Inhibition of Regenerating Axons in the Zebrafish Optic Nerve

Abstract: In contrast to mammals, lesioned axons in the zebrafish (ZF) optic nerve regenerate and restore vision. This correlates with the absence of the NogoA-specific N-terminal domains from the ZF nogo/rtn-4 (reticulon-4) gene that inhibits regeneration in mammals. However, mammalian nogo/rtn-4 carries a second inhibitory C-terminal domain, Nogo-66, being 70% identical with ZF-Nogo66. The present study examines, (1) whether ZF-Nogo66 is inhibitory and effecting similar signaling pathways upon Nogo66-binding to the No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
47
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 67 publications
8
47
0
2
Order By: Relevance
“…Interestingly, in zebrafish, CSPGs appear not to inhibit, but rather to guide optic nerve regeneration in zebrafish (Becker and Becker, 2002). Furthermore, orthologues of mammalian growth-inhibitory molecules and their receptors, like Nogo-family members, have been identified in fish (Abdesselem et al, 2009;Diekmann et al, 2005;Klinger et al, 2004). However, zebrafish NogoA lacks a specific domain that inhibits neurite outgrowth in mammals (Diekmann et al, 2005).…”
Section: Regeneration-permissive Features Of the Adult Zebrafish Telementioning
confidence: 99%
“…Interestingly, in zebrafish, CSPGs appear not to inhibit, but rather to guide optic nerve regeneration in zebrafish (Becker and Becker, 2002). Furthermore, orthologues of mammalian growth-inhibitory molecules and their receptors, like Nogo-family members, have been identified in fish (Abdesselem et al, 2009;Diekmann et al, 2005;Klinger et al, 2004). However, zebrafish NogoA lacks a specific domain that inhibits neurite outgrowth in mammals (Diekmann et al, 2005).…”
Section: Regeneration-permissive Features Of the Adult Zebrafish Telementioning
confidence: 99%
“…RTN1 belongs to a family of RTN proteins (RTN1-RTN4), which were first described in neuroendocrine cells to localize primarily to the ER membrane as ER-shaping proteins (8, 25). RTN4, also named Nogo, has previously been the only well-characterized member in the RTN family that has been shown to induce apoptosis, inhibit neuronal regeneration, and regulate protein trafficking (1,8,17). Our results showed that of the three RTN1 isoforms (RTN1A, RTN1B, and RTN1C), only RTN1A expression was increased in the kidney of both human and murine models of kidney disease and that the intensity of RTN1A staining in the tubulointerstitial compartment was correlated with the progression of DN.…”
mentioning
confidence: 99%
“…It recognized the peptide against which it was raised and 210 kDa Nogo‐A in Western blots with lysates of cultured oligodendrocytes (Oertle et al, ) and binds to GST‐delta20 and GST‐M1–4 as well as to delta20 and M1–4 after cleavage of GST in our present study (Figure ). pAB IK964 is a polyclonal AB from a rabbit which was immunized with the His‐tagged Nogo‐66 peptide of zebrafish Rtn4a (Abdesselem et al, ; Pinzon‐Olejua et al, ; Claudia Stuermer Lab Universität Konstanz; Germany Cat# Rtn4a, RRID:AB_2636940). The specificity was shown in lysates of zebrafish embryos after injections of Rtn4a‐specific and control morpholinos, respectively, into the yolk at early stages of development, and by immunostainings at increasing developmental stages as well as in the adult optic nerve after lesion (Abdesselem et al, ).…”
Section: Methodsmentioning
confidence: 99%